S.A. Woods & Co.s' Machinery Depot; Newcomb & Brown, Apothecaries; Delaporte & Blumberg, Chairs; International Hotel - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of S.A. Woods & Co.s' Machinery Depot; Newcomb & Brown, Apothecaries; Delaporte & Blumberg, Chairs; International Hotel from the 1870 Boston City Directory